Determination of critical micelle concentration of cetyltrimethylammonium bromide in presence and absence of KCl and NaCl in aqueous media at room temperature by viscosity measurement - Jha, Kabita; Bhattarai, Ajaya; Chatterjee, Sujeet Kumar (BIBECHANA, 2014)
NOTE: The correct reference list was added to this article on 08/07/2014. Viscosity measurement of cetyltrimethylammonium bromide in presence and in absence of KCl and NaCl in aqueous media is done. The results showed a sharp increase in viscosity with increase in concentration of cetyltrimethylammonium bromide. Also, the viscosity increases with addition of salts. The viscosity of cetyltrimethylammonium bromide is found more in presence of KCl than NaCl in aqueous media. In presence of monovalent salts, the critical micelle concentration (cmc) value decreases which is explained on the basis of nature and ionic strength of the added ion. The graphs of viscosity versus concentration are used in determining the critical micelle concentration (cmc). DOI: http://dx.doi.org/10.3126/bibechana.v11i0.10392 BIBECHANA 11(1) (2014) 131-135